Crusade and Jihad : the thousand-year war between the Muslim world and the global north - Polk, William R. (William Roe), 1929-2020 (Henry L. Stimson lectures, Yale University., 2018)
Crusade and Jihad is the first book to encompass, in one volume, the entire history of the catastrophic encounter between the Global North - China, Russia, Europe, Britain, and America - and Muslim societies from Central Asia to West Africa. William R. Polk draws on more than half a century of experience as a historian, policy planner, diplomat, peace negotiator, and businessman to explain the deep hostilities between the Muslim world and the Global North and show how they grew over the centuries. Polk shows how Islam arose and spread across North Africa into Europe, climaxed in the vibrant and sophisticated caliphate of al-Andalus in medieval Spain, and was the bright light in a European Dark Age. Simultaneously, Islam spread from the Middle East into Africa, India, and Southeast Asia. But following the Mongol invasions, Islamic civilization entered a decline while Europe began its overseas expansion. Portuguese buccaneers dominated the Indian Ocean; the Dutch and the English established powerful corporations that turned India and Indonesia into colonies; Russian armies pushed down the Volga into Central Asia, destroying its city-states; and the Chinese Qing dynasty slaughtered an entire Central Asian people. Britain crushed local industry and drained off wealth throughout its vast colonies. Defeated at every turn, Muslims tried adopting Western dress, organizing Western-style armies, and embracing Western ideas. None of these efforts stopped the conquest. For Europe and Russia, the nineteenth century was an age of colonial expansion, but for the Muslim world it was an age of brutal and humiliating defeat. Millions were driven from their homes, starved, or killed, and their culture and religion came under a century-long assault. In the twentieth century, brutalized and disorganized native societies, even after winning independence, fell victim to "post-imperial malaise," typified by native tyrannies, corruption, and massive poetry. The result was a furious blowback. A sobering, scrupulous, and frank account of imperialism, colonialism, insurgency, and terrorism, Crusade and Jihad is history for anyone who wishes to understand the civilizational conflicts of today's world. -- from dust jacket